2021
DOI: 10.1007/s12599-021-00686-z
|View full text |Cite
|
Sign up to set email alerts
|

Not All Doom and Gloom: How Energy-Intensive and Temporally Flexible Data Center Applications May Actually Promote Renewable Energy Sources

Abstract: To achieve a sustainable energy system, a further increase in electricity generation from renewable energy sources (RES) is imperative. However, the development and implementation of RES entail various challenges, e.g., dealing with grid stability issues due to RES’ intermittency. Correspondingly, increasingly volatile and even negative electricity prices question the economic viability of RES-plants. To address these challenges, this paper analyzes how the integration of an RES-plant and a computationally int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…An analysis of the integrated energy system combining a renewable source power plant and a computational data center has demonstrated that such an approach offers higher net present value than the standalone power plant solution. 51 However, the main difference between a conventional data center and bitcoin is the feasible interruptibility of the latter. Similar conclusions were reached for specific analyses of wind power in Brazil 52 and both wind and solar power in Texas.…”
Section: Renewable Energymentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the integrated energy system combining a renewable source power plant and a computational data center has demonstrated that such an approach offers higher net present value than the standalone power plant solution. 51 However, the main difference between a conventional data center and bitcoin is the feasible interruptibility of the latter. Similar conclusions were reached for specific analyses of wind power in Brazil 52 and both wind and solar power in Texas.…”
Section: Renewable Energymentioning
confidence: 99%
“…Bitcoin mining and operations of the likes of Amazon Web Services, Google, or Netflix fit the bill. An analysis of the integrated energy system combining a renewable source power plant and a computational data center has demonstrated that such an approach offers higher net present value than the standalone power plant solution . However, the main difference between a conventional data center and bitcoin is the feasible interruptibility of the latter.…”
Section: Bitcoin In Greenhouse Gas Emissions and Renewable Energymentioning
confidence: 99%
“…Research stream on energy informatics and CO 2 emission tracing applications is widespread, ranging, among others, from topics concerning energy efficiency (Watson et al 2010), energy flexibility, e.g., provided by electric vehicles (Holly et al 2020) or its exploitation via artificial intelligence (Fridgen et al 2022;Hanny et al 2022), over data centers that are enabled to act in the sense of the energy transition (Klingert 2018;Fridgen et al 2021), to the potential of IS for future energy data spaces to improve collaboration and energy systems' robustness (Körner et al 2022). In 2014, Goebel et al provided an overview of goals, themes, and use cases of Energy Informatics research that distinguishes relevant topics between "smart energy-saving systems" and "smart grids" (Goebel et al 2014).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Fridgen et al [29], like many other researchers of the past few years, concentrate on the massive amount of energy consumed by two intensive and widespread computing processes: machine learning and cryptocurrency mining on systems, such as Bitcoin (the most widely traded and mined cryptocurrency, the precursor to the current age of blockchain-based applications [30]). Based on the findings of Fridgen et al, there is some hope though that the existence of these high-cost systems would drive further investment into renewable energy sources.…”
Section: The Environmental Impact Of Computingmentioning
confidence: 99%